2018
DOI: 10.1111/jfd.12814
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of co‐infections with pathogens associated with gill disease in Atlantic salmon during an amoebic gill disease outbreak

Abstract: Gill diseases are a complex and multifactorial challenge for marine farmed Atlantic salmon. Co-infections with putative pathogens are common on farms; however, there is a lack of knowledge in relation to the potential effect co-infections may have on pathology. The objective of this study was to determine the prevalence and potential effects of Neoparamoeba perurans, Desmozoon lepeophtherii, Candidatus Branchiomonas cysticola, Tenacibaculum maritimum and salmon gill poxvirus (SGPV) during a longitudinal study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 41 publications
(88 reference statements)
6
41
0
Order By: Relevance
“…Many wild and cultured fish species host this bacterium (Toranzo, Magarinos, & Romalde, ). Among salmonids, T. maritimum‐ related infection has been reported in Chinook salmon in the USA (Chen, Henry‐Ford, & Groff, ) and recently New Zealand (Brosnahan, Munday, Ha, Preece, & Jones, ), farmed Atlantic salmon in western Canada (Ostland, Morrison, Ferguson, & H., ), Australia (Soltani, Munday, & Burke, ), Ireland (Downe et al, ; Fringuelli et al, ) and Chile (Apablaza et al, ). Disease caused by this agent has some species‐specific pathological differences.…”
Section: Synthesis Of Information About Infectious Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many wild and cultured fish species host this bacterium (Toranzo, Magarinos, & Romalde, ). Among salmonids, T. maritimum‐ related infection has been reported in Chinook salmon in the USA (Chen, Henry‐Ford, & Groff, ) and recently New Zealand (Brosnahan, Munday, Ha, Preece, & Jones, ), farmed Atlantic salmon in western Canada (Ostland, Morrison, Ferguson, & H., ), Australia (Soltani, Munday, & Burke, ), Ireland (Downe et al, ; Fringuelli et al, ) and Chile (Apablaza et al, ). Disease caused by this agent has some species‐specific pathological differences.…”
Section: Synthesis Of Information About Infectious Agentsmentioning
confidence: 99%
“…Although both adults and juveniles may be affected by T. maritimum , differences in the susceptibility of some fish species to the disease are age‐dependent (Avendaño‐Herrera, Toranzo, & Magariños, ). An increased prevalence and severity of the disease is likely to occur at higher temperatures and salinities, as well as in association with poor water quality (Downes et al, ; Toranzo et al, ). The bacterium can readily transfer horizontally within a population, and the agent has been isolated from sediment, the surface of tanks, and from water cultures that have been exposed to infected stocks (Frisch, Småge, & Vallestad et al, ).…”
Section: Synthesis Of Information About Infectious Agentsmentioning
confidence: 99%
“…Importantly, coinfection (multiple agent species in one host) and superinfection (multiple agent genotypes in one host) are common in wild animals and the dynamics of these communities are linked to host fitness outcomes (Martin et al 2012;Alizon et al 2013;Sofonea et al 2015). Host health and performance, especially in the wild, can be impacted by shifts in coinfection or superinfection prior to the occurrence of detectable or typical tissue changes (pathology) associated with disease (Brassard et al 1982;Wiik-Nielsen et al 2016;Downes et al 2018). This complexity warrants an approach beyond traditional diagnostics to characterize transmission events that can influence disease processes in wild fish.…”
Section: Introductionmentioning
confidence: 99%
“…In Ireland, Downes et al [43] observed that between 12 and 16 weeks after seawater transfer, colonization of the gills by D. lepeophtherii, Candidatus B. cysticola, T. maritimum, SGPV and N. perurans commenced, and by week 16 of marine production, each of the pathogens was detected. D. lepeophtherii and Candidatus B. cysticola were by far the most prevalent of the potential pathogens detected.…”
Section: Pathogens Involved In Cgdmentioning
confidence: 99%
“…However, noninfectious disorders due to harmful algae blooms (HABs) and other challenges also play roles in the mortalities attributable to CGD [43]. Several species of marine phytoplankton have been recorded to be associated with fish mortalities, including Karenia mikimotoi, which has been implicated in Atlantic salmon mortalities in Ireland, Scotland and Norway [44][45][46][47].…”
Section: Pathogens Involved In Cgdmentioning
confidence: 99%